New and developing therapies for AL amyloidosis. (22nd January 2017) - Zumbo, Giulia; Sadeghi-Alavijeh, Omid; Hawkins, Philip N.; Fontana, Marianna
ABSTRACT: Introduction : Systemic light-chain (AL) amyloidosis is an infiltrative disorder associated with an underlying plasma cells dyscrasia, in which monoclonal immunoglobulin light chains accumulate in an abnormal misfolded form as amyloid fibrils in the extracellular space. Symptoms and prognosis are governed by which organs are affected, and cardiac involvement is the major determinant of survival. Diagnosis requires demonstration of amyloid deposition and confirmation of the fibril protein type. Areas c overed : This review will focus on the available treatments for systemic AL amyloidosis and on new drug targets and therapeutic approaches. Expert opinion : At present, the choice of upfront treatment lies between autologous stem cell transplantation (ASCT) and combination chemotherapy. Chemotherapy agents include dexamethasone, melphalan, cyclophosphamide, thalidomide, bortezomib, lenalidomide, bendamustine in various combinations. Few randomized controlled trials have been performed in AL amyloidosis and treatment has been substantially influenced by clinical practice in myeloma. It has become clear that the best prospects of survival and preservation or improvement in amyloid related organ function require as near complete suppression as possible of the underlying hematological disorder. Future directions include therapies designed to target amyloid deposits directly, in particular anti-amyloid antibodies which are now well advanced in development and are showing great potential.